PENERAPAN PHBS UNTUK MENCEGAH PENULARAN COVID-19 PADA KELAS IBU HAMIL DI POSYANDU YANG ADA DI WILAYAH PUSKESMAS KAWALU KOTA TASIKMALAYA - NENI; LULU YULIANI; ANITA EKA PUTRI; REVI MAINAKI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
PHBS is all health behavior that is carried out with awareness so that family members or families can help themselves in the health sector and play an active role in health activities in the community (DEPKES RI, 2010). PHBS must be implemented in various settings, one of which is PHBS at the Health Care Facility (POSYANDU). Pregnant women are a group of people who are at risk of being vulnerable to various health problems. Among them are susceptible to contracting infectious diseases, one example is currently an outbreak of COVID 19, therefore we are in this dedication will provide education about "the application of phbs in posyandu for pregnant women class which aims to prevent pregnant women from contracting covid 19, we hope that this PHBS can be implemented in daily life, in daily activities so that the community, especially pregnant women, have a good health status. For this reason, the TOT for Posyandu cadres we do for Posyandu cadres in the area of ​​Puskesmas Kawalu, Tasikmalaya City aims to improve the quality of life by increasing knowledge and awareness to behave in a clean and healthy life (PHBS), as well as applying it to the class of pregnant women at existing Posyandu in wila well, Puskesmas Kawalu, Tasikmalaya City.